Corrigendum. (December 2014) - Unknown
Corrigendum to ' Agent-based simulation approach to understanding the interaction between employee behaviour and dynamic tasks ', Simulation: Transactions of the Society for Modeling and Simulation International (2010); [Epub ahead of print] [DOI:10.1177/0037549710385745 ].